THE ANALYSIS OF DIRECTIVE SPEECH ACT DURING DISTANCE LEARNING - Yan Imam Santoso; Prasetyawan Aji Sugiharto (Jurnal Ilmiah Spectral, 2022)
Since the whole world has experienced the Covid-19 pandemic, which has an impact on the education system; it has changed temporarily for an indefinite period. Learning carried out in Indonesia in particular was changed from face-to-face meetings to distance learning. Interaction or communication between teachers and students is carried out online or utilizing technology, both orally and in writing. Speech acts also influence distance learning, where the expressions are given by the teacher becomes a part that has power in regulating the success of distance learning. This study aims to describe the types of directive speech acts performed by teachers to elementary school students. This research is a qualitative descriptive studywith a population of elementary school teachers in Batang, Central Java. The researcher took a sample of 10 teachers who were taken randomly. The results of the study found that directive speech acts with the type of command expression are often used by teachers in distance learning with 16 expressions. The conclusion of this research is the expression of command is an expression that is often spoken by the teacher in delivering the material. Through this research, it is hoped that it can provide brief information that the teacher's directive speech acts are part of the process of delivering material or information.